Crystallization and preliminary X-ray diffraction analysis of a soluble domain of the putative zinc transporter CzrB from Thermus thermophilus - CAFFREY, MARTIN (My University, 2007)
CzrB is a putative zinc transporter from Thermus thermophilus. The protein is proposed to consist of a hexahelical transmembrane domain with a cytosolic extramembranal C-terminus. The latter 92-residue fragment may be expressed free and may function independently of the full-length integral membrane protein. A 6 His-tagged form of the water-soluble fragment has been overexpressed in Escherichia coli and diffraction-quality crystals of the tagged and tag-free variants have been grown. Preliminary X-ray analyses of tag-free fragment crystals with (2.2 A ? resolution) and without zinc ions (1.7 A ? resolution) reveal that the former has at least two zinc ions bound per monomer.
PUBLISHED
PMID: 17671365
Keywords: Biophysics; Thermus thermophilus; diffraction analysis; Nanoscience & Materials